Zn vacancy induced ferromagnetism in K doped ZnO. Issue 45 (2nd November 2015) - Wang, Yiren; Piao, Jingyuan; Xing, Guozhong; Lu, Yunhao; Ao, Zhimin; Bao, Nina; Ding, Jun; Li, Sean; Yi, Jiabao
Abstract : K doped ZnO shows room temperature ferromagnetism from both theoretical and experimental studies. This ferromagnetism is mainly attributed to the formation of the Zn vacancy. The K dopants can stabilize the Zn vacancy by forming a defect complex and K substitution can induce magnetism via lattice distortion. Abstract : Using first-principle calculations, we studied the mechanism of the magnetic properties of K doped ZnO. The results show that the magnetic moment originates from the O 2p hole states around Zn vacancies. K substitution in Zn can also induce magnetism, which is due to the formation of the partial Zn vacancy induced by lattice distortion. Ferromagnetic ordering occurs via p–p coupling, which is mediated by the holes that result from K doping. Further investigation indicates that a single Zn vacancy has a high formation energy, whereas the formation energy of a defect complex composed of K interstitial (Kint ), K substitutional (KZn ) and zinc vacancy (VZn ) is significantly reduced. In addition, K dopants prefer a large separation, which suggests uniform distribution. Experimentally, K doped ZnO nanorods were fabricated using a hydrothermal method and room temperature ferromagnetism was observed. 2 at% K doped ZnO has the largest saturation magnetization, which is consistent with first-principle calculations.